Pengaruh Literasi Keuangan Terhadap Orientasi Kewirausahaan Sosial dan Kinerja Usaha Bank Sampah di Yogyakarta - Ni Luh Gde Ana Pertiwi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The condition of waste management in Indonesia, including in Yogyakarta, is becoming an increasingly complex problem along with increasing population and urbanization. Public awareness of the importance of waste sorting and management is also still low, even though the city government has attempted various programs related to 3R-based waste management (Reduce, Reuse, Recycle). The waste bank in Yogyakarta is one of the innovative efforts developed to overcome the waste problem and provide economic value from the waste produced by the community. The waste bank in Yogyakarta is a model of social entrepreneurship. With good management, waste banks can function as local economic centers that generate income from waste processing by incorporating the concept of social entrepreneurship orientation. Financial literacy has a very important role in supporting waste bank operations, especially in developing social entrepreneurial orientation and improving their performance. Waste banks, as entities that manage waste with social and environmental goals, must also manage finances well to ensure sustainability and a wider positive impact. The sampling technique uses saturated samples. Analytical tools This research uses descriptive analysis techniques and quantitative analysis techniques with structural equation models or Structural Equation Modeling (SEM), especially Partial Least Square (PLS). The results of this research are 1) Financial Literacy has no effect on waste bank business performance; 2) Social Entrepreneurship Orientation has a positive effect on waste bank business performance; 3) Social Entrepreneurship Orientation fully mediates the relationship between Financial Literacy and waste bank business performance